The Influence Of Various Factors On The Formation Of The Knee Reflex (Global Scientific Review, 2024)
The development of the knee-jerk reflex is a reliable indicator of neurological health. This reflex is tested by palpating the patellar tendon under the kneecap, which results in an involuntary jerk of the leg. The knee-jerk reflex is a key indicator of the integrity of the spinal cord and peripheral nerves, particularly between the L2 and L4 vertebrae. The Development Strategy for 7 priority areas of development of the Republic of Uzbekistan for 2022-2026, adopted at the initiative of the President of the Republic of Uzbekistan, identifies important areas related to the intellectual, aesthetic and physical development of students based on continuous education in our country, which ensures that all conditions are created for students to conduct experiments and study the topics in more depth at the Tashkent Medical Academy.